GROWING WINTER WHEAT IN VARIOUS SHORT-ROTATION CROP ROTATION MODELS ADAPTED TO THE CONDITIONS OF THE STEPPE ZONE OF UKRAINE - Yuriy Mashchenko; Iryna Sokolovska (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis)
The need for developing new models of modern crop rotations is justified by the current conditions of agricultural and economic development. Research conducted in the conditions of the Northern Steppe of Ukraine confirmed the impact of crop rotation factors and fertilization on the yield, product quality, and economic efficiency of winter wheat cultivation. It was established that growing winter wheat in a grain-fallow-arable crop rotation model with 20 % soybean saturation contributed to achieving a higher yield level, with a difference compared to the grain-arable crop rotation model with 40 % soybean saturation - 0.59 t ha-1 or 9.0 %, and compared to model with 60 % soybean saturation - 0.81 t ha-1 or 12.7 %. Growing winter wheat in crop rotation model with 20 % soybean saturation under an organo-mineral biologized fertilization system contributed to achieving maximum yield at the level of 7.93 t ha-1. The implementation of biologized mineral and organo-mineral fertilization systems in grain-arable crop rotation models (60 % and 40 % soybean saturation) ensured a yield formation at the level of 6.52-7.40 t ha-1 and 6.71-7.54 t ha-1, respectively. The highest grain quality, corresponding to Class II, was also observed in the grain-fallow-arable crop rotation model, but under a mineral biologized fertilization system. In other crop rotation models and fertilization variants, the grain quality was lower and corresponded to Classes III and IV. The biologicalization of recommended crop rotations for the Ukrainian Steppe contributed to achieving significantly higher winter wheat grain yields regardless of their structure and soybean saturation. Higher economic efficiency was achieved by growing winter wheat in a grain-fallow-arable crop rotation with 20 % soybean saturation based on an organo-mineral fertilization system, which contributed to obtaining the highest conditional net profit at the level of 37 334 UAH ha-1 with a profitability of 156.2 %.